Blood Pressure Increase With Impaired Glucose Tolerance in Young Adult American Blacks - Falkner, Bonita; Sherif, Katherine; Sumner, Anne E.; Kushner, Harvey (Hypertension (Dallas, Tex. 1979), 1999)
Hypertension and non-insulin-dependent diabetes mellitus are more prevalent in blacks than whites. The convergence of these 2 disorders augments the expression and severity of cardiovascular disease. The purpose of this study was to determine whether alterations in glucose metabolism are related to an increase in blood pressure (BP). This study was conducted on 304 nondiabetic blacks (mean age=32 years). Measurements in all subjects included BP, anthropometric measures, oral glucose tolerance test, insulin clamp to measure insulin sensitivity, and plasma lipids. The sample was stratified according to plasma glucose on oral glucose tolerance test to normal glucose tolerance (NGT), impaired glucose tolerance (IGT), and diabetes mellitus (DM). A 2-way ANOVA was performed to determine differences between the metabolic groups. With the use of American Diabetic Association criteria, 20.4% of the samples were classified as IGT and 5.9% were diabetic. A significant increase in BP existed from NGT to IGT to DM, which was stronger in women than men (systolic blood pressure in womenNGT=122, IGT=127, and DM=140 mm Hg, P<0.001) with a significant linear trend (P<0.001). With the use of body mass index as a covariate, the group difference in BP remained significant (P=0.006). Measures of insulin sensitivity demonstrated significant metabolic group differences (P<0.001) with a linear trend (P<0.001) of decreasing insulin sensitivity from NGT to DM. These results indicate that early alterations in glucose metabolism effects an upward shift in BP. The higher BP in IGT and DM may be due to vascular endothelial cell resistance to insulin action.